Assessment of Water Resources Carrying Capacity Based on Principal Component Analysis and System Dynamics: A Case Study of Qingyang City - WANG Qian, YUAN Bo, WU Jian, LIU Wen-shi, WU Yan (长江科学院院报)
[Objectives] This study aims to overcome the limitations of traditional static evaluation methods by developing a multidimensional assessment framework for water resource carrying capacity with spatiotemporal continuity. It seeks to reveal the evolution patterns of regional water resources carrying capacity and propose optimized regulation schemes. [Methods] A dynamic-static analytical framework combining principal component analysis (PCA) and system dynamics (SD) modeling was applied, with Qingyang City in Gansu Province—an area relatively short on water resources—as the study area. First, using data from 21 indicators from 2012 to 2022, PCA was used to extract principal components (cumulative variance contribution rate >85%) to establish a comprehensive evaluation system for water resources carrying capacity and identify key influencing factors. Subsequently, a complex dynamic model of water resources system was established by dividing the system into socioeconomic, water supply-demand, and ecological subsystems. The dynamic changes in water supply and demand under different development scenarios were simulated. Four optimization schemes were designed: status quo development (baseline), water-saving, wastewater treatment, and integrated coordinated development. Their optimization effects on regional water resources carrying capacity were evaluated from the perspectives of water demand control, water supply efficiency improvement, and coordinated governance. [Results] (1) The water resources carrying capacity of Qingyang City significantly declined, with an annual average decrease rate of 18.78% from 2015 to 2022. PCA revealed that socioeconomic development (population growth rate, GDP per capita), water resource allocation efficiency (crude oil processing volume, water resources per capita), and ecological development level (green coverage rate in built-up areas) were the key driving factors, contributing 35.2%, 28.6%, and 19.3% to the principal component loadings, respectively. (2) Dynamic simulations showed that under the status quo development scheme (scheme 1), water shortage in 2035 increased by 47.8% compared to the baseline year (2012), with a supply-demand gap expanding to 123 million m3. The water-saving scheme (scheme 2) reduced the shortage by 11.9% through improved reuse rates, but due to the inflexible growth in water demand, the imbalance remained significant. The wastewater treatment scheme (scheme 3) reduced water shortage by 15.1% by increasing reuse rate to 55%, demonstrating a 3.2-percentage-point greater improvement compared to scheme 2. The integrated coordinated development scheme (scheme 4) implemented a synergistic “water-saving and pollution-control” strategy, optimizing demand-side control (improving industrial water-saving and agricultural irrigation efficiency) and enhancing supply-side circulation (wastewater reuse rate at 60%). This ultimately reduced the water shortage in 2035 by 16.7% compared to scheme 1, lowered total water demand by 19.4%, and narrowed the supply-demand gap to 51 million m3. [Conclusions] This study innovatively establishes an analytical paradigm integrating “historical diagnosis, dynamic early warning, and strategy optimization.” The degradation of water resources carrying capacity in oil and gas resource-based cities is essentially a manifestation of the imbalance between energy development, economic growth, and ecological protection. An integrated development strategy that includes water-saving, pollution control, and economic adjustments proves effective in alleviating water resource pressure through dual supply-demand adjustments. Future water management in Qingyang City requires curbing its current development trends promptly and regulating key guiding factors. Among the four projected schemes, the integrated coordinated development scheme performs optimally.